Aspek Sosial-Intelektual Observatorium dalam Islam - Muhammad Qorib (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2019)
The Observatory is a scientific institution in Islamic civilization that has a strategic function and position in people's lives. In addition to the means of accurate time and location of worship, the observatory also functions as a science education institution that integrates faith, Islam, science, and empiric. In the context of Islamic civilization, the observatory is a miniature advance of a civilization (nation).